STRATIGRAPHY, SEDIMENTARY STRUCTURES, AND TEXTURES OF THE LATE NEOPROTEROZOIC DOUSHANTUO CAP CARBONATE IN SOUTH CHINA - Jiang G.; Kennedy M.J.; Christie-Blick N.; Wu H.; Zhang S. (My University, 2006)
The 3- to 5-m-thick Doushantuo cap carbonate in south China overlies the glaciogenic Nantuo Formation (ca. 635 Ma) and consists of laterally persistent, thinly laminated and normally graded dolomite and limestone indicative of relatively deep-water deposition, most likely below storm wave base. The basal portion of this carbonate contains a distinctive suite of closely associated tepee-like structures, stromatactis-like cavities, layer-parallel sheet cracks, and cemented breccias. The cores of tepees are composed of stacked cavities lined by cements and brecciated host dolomicrite. Onlap by laminated sediment indicates synsedimentary disruption of bedding that resulted in a positive seafloor expression. Cavities and sheet cracks contain internal sediments, and they are lined by originally aragonitic isopachous botryoidal cements with acicular radiating needles, now replaced by dolomite and silica. Pyrite and barite are common, and calcite is locally retained as a primary mineral. These features share morphological and petrographic attributes with modern and ancient methane seeps in which methane gas and fluids provide both a force for physical disruption from buoyancy and a source of alkalinity for significant cementation. The presence of δ13C values as low as -41‰ in well preserved limestone crusts and cements within and immediately above the tepee-like structures provides unequivocal evidence for methane influence, and the widespread distribution of identical sedimentary structures and paragenetic cement sequences across the entire basin at the same basal cap carbonate level is consistent with gas hydrate destabilization and the development of methane seeps as a result of postglacial warming of the ocean. Considering the broad distribution of similar features at the same stratigraphic level in other cap carbonates globally, we suggest that the late Neoproterozoic postglacial methane release may have influenced the oceanic oxygen level as well as contributed to postglacial warming via the greenhouse effects of methane. Copyright © 2006, SEPM (Society for Sedimentary Geology).
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская